PEMBUATAN ASAM OKSALAT DARI ALANG-ALANG (Imperata Cylindrica) DENGAN METODE PELEBURAN ALKALI - Iriany, Andrew Faguh Sitanggang, Rahmad Dennie A. Pohan (Jurnal Teknik Kimia USU, 2015)
Imperata grassland is one of the wild plant which have a low economic value but containing high cellulose. Therefore it is potentially to be used as raw material for  oxalic acid manufacturing. The oxalic acid can be produced from imperata grassland through 4 steps: alkaline hydrolysis, precipitacion, acidification and crystallization. Experiments are carried out in a three necks glass equipped with thermometer, mixer, heater and condenser. Cooking solution NaOH  were varied 3,5 N; 4 N  and 4,5 N and cooking time 50, 60, 70 and 80 minutes. According to the result from the experiment, at the condition 98oC of cooking temperature, the highest yield of oxalic acid about 44,39% is obtained at 4 N concentration of sodium hydroxide and 60 minute of cooking time. Oxalic acid produced has 104oC of melting point  and 1,2 of degree of acidity (pH).